Development of a Gastropod Diversity E-booklet as a Learning Media for High School Students - Rostikawati, Raden Teti; Lamis, Shabira; Prasaja, Dimas (Journal Of Biology Education Research (JBER), 2025)
The study of Gastropod diversity in Cibuaya is very important, since Gastropods are the most important organisms in the food chain in aquatic ecosystems. To understand Gastropods, students need electronically supported learning aids in the form of e-booklet. One of the very important roles of e-booklets students can access e-booklets anytime, anywhere on their devices. The aim of this research is to develop a research-based electronic booklet for the identification of gastropod diversity, based on the findings from the identification of gastropods at Cibuaya Beach, Sukabumi. The development method used in this research is the 4-D model, which includes definition, design, development, and dissemination. This research was realized by developing the research results into an electronic brochure on gastropod diversity at Cibuaya Beach, Ujung Genteng, Sukabumi. Validation of the e-booklet was carried out by three Lecturers who were experts in material content, language, and media, and three Biology teachers to validate regarding the content of the material which is adapted to the material at school . The results of the validation test produced an average score of 86%. This score indicates that the E-booklet learning support falls into the very viable category and can be used in learning activities.